Status of Living with Parents, Smartphone Addiction, and Problematic Eating Behavior in Adolescents - Kabbaro, Hurriyyatun; Wulan, Nayang; Hamiyati (Journal of Family Sciences, 2023)
Excessive intensity of smartphone use can disrupt eating behavior in adolescents. This study aims to analyze the relationship between smartphone addiction and problematic eating behavior. This research involved 230 junior high school students in Jakarta. The research design uses a cross-sectional study. Data were analyzed using Pearson's correlation and Independent Sample T-Test. The results of the Chi-Square test show that the Asymp. Sig. (2-sided) for the smartphone addiction category with a problematic eating behavior category is 0.000 (p<0.05). The correlation test result shows a relationship between the smartphone addiction category and the duration of smartphone use in the morning, afternoon and evening. The Chi-Square Test shows a relationship between the categories of problematic eating behavior and the duration of smartphone use in the morning and afternoon. The Independent Sample T-Test result shows a significant difference in the daily-life disturbance and positive anticipation dimensions between respondents who live with their complete parents (TOL) and those who do not live with their complete parents (TTOL). The result shows a significant positive relationship between smartphone addiction and problematic eating behavior (r=0.711; p=0.000). Adolescents need to raise awareness to use smartphones as needed. In addition, adolescents are advised to adopt healthy eating habits to optimize their growth.